Reliable and Energy-aware Mapping of Streaming Series-parallel Applications onto Hierarchical Platforms - Gou, Changjiang; Benoit, Anne; Chen, Mingsong; Marchal, Loris; Wei, Tongquan (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
Streaming applications come from various application fields such as physics, and many can be represented as a series-parallel dependence graph. We aim at minimizing the energy consumption of such applications when executed on a hierarchical platform, by proposing novel mapping strategies. Dynamic voltage and frequency scaling (DVFS) is used to reduce the energy consumption, and we ensure a reliable execution by either executing a task at maximum speed, or by triplicating it. In this paper, we propose a structure rule to partition the series-parallel applications, and we prove that the optimization problem is NP-complete. We are able to derive a dynamic programming algorithm for the special case of linear chains, which provides an interesting heuristic and a building block for designing heuristics for the general case. The heuristics performance is compared to a baseline solution, where each task is executed at maximum speed. Simulations demonstrate that significant energy savings can be obtained.